Use of psychotropic medications during pregnancy: perception of teratogenic risk among physicians in two Latin American countries - Cantilino,Amaury (2014)
Objective: Pregnant women and their health care professionals commonly believe that use of medications during pregnancy may be harmful to the unborn fetus. The objective of this study was to evaluate the risk perception of psychotropic drug use in pregnancy among physicians in different medical specialties. Method: This was a convenience survey conducted at outpatient clinics in the cities of Recife, Brazil, and La Plata, Bahía Blanca, and Buenos Aires, Argentina. Physicians who agreed to participate were asked to rate their perception of teratogenic risk among different classes of drugs, which included antidepressants, antipsychotics, anticonvulsants, and benzodiazepines. Results: Two hundred and thirty-eight physicians completed the survey (response rate, 98%). These included psychiatrists, obstetricians, neurologists, cardiologists, gastroenterologists, and general practitioners. Among different specialties, a minority of psychiatrists perceived psychotropic drugs to be highly teratogenic (antidepressants, 12.5%; antipsychotics, 15%; benzodiazepines, 25%) as compared with other specialties (p < 0.003 for each drug class). There was no difference in perceived risk of antiepileptic drugs among specialties, including psychiatrists. Conclusion: The risk associated with use of psychotropic drugs in pregnancy was overestimated by physicians of all medical specialties, except psychiatry. All physicians should be aware of the safety/risk of psychotropic agents in pregnancy, as they may be required to give advice and/or prescribe these drugs to pregnant women.